13-VALENT PNEUMOCOCCAL CONJUGATE VACCINE - V. K. Tatochenko; L. S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2012)
The data on efficacy and safety of 7- and 13-valent pneumococcal conjugate vaccines are shown in this article. The authors have analyzed the experience of immunization with 13-valent vaccine Prevenar. Post-vaccination reactions were mild or moderate consisting in localized tenderness in site of injection and febrile fever and were not registered more frequently than in cases of 7-valent vaccine usage. There were no severe post-vaccination side-effects. This facts confirm low reactogenicity of this vaccine and the possibility of its usage in children.